The noise spectrum influence on Noise-Induced Hearing Loss prevalence in workers - Boger,Marlene Escher (2009)
Noise Induced Hearing Loss (NIHL) is an insidious and cumulative disease that worsens over the years with work-related noise exposure. AIM: To evaluate the noise spectrum influence on NIHL prevalence in workers. MATERIALS AND METHODS: This a cross-sectional historical cohort carried out in steel mills, lumber mills and marble shops, with noise levels above 85dB, in which we evaluated the auditory thresholds for frequencies from 250Hz to 8,000Hz. To evaluate the work environment, we observed the entire setting, aiming at checking sound intensities in an eighth frequency filter. RESULTS: We carried out 192 hearing threshold evaluations after an occupational anamnesis. Concerning NIHL, we noticed that 49% of the audiometry results presented hearing deterioration in the acute frequencies. We studied the mean values and standard deviations for frequencies over 3,000Hz, in all workers, and we observed that the highest average values were in the frequency of 6,000Hz. We did not notice any association among frequency bands carrying intense noise levels and the hearing damage frequency. CONCLUSION: Noise intensity seems to be the main risk factor for loss hearing, regardless of frequency range.